Low-pass CMOS Sigma-Delta Converter - Diogo Dinis da Fonseca (2018)
The growing need to provide better health for the population requires the development of new and better medical devices. Portable devices for the analysis of biological signals, such as the electrocardiogram or electroencephalogram, is nowadays an important development, helping health professionals to come up with fast diagnoses on the field, or even for use by citizens who require constant vigilance . Developing these devices brings new challenges to the scientific community, namely at the analog/digital interface, the quality of data and power consumption. In order to design a good medical device it is necessary an analog/digital converter for low frequencies, with low power consumption and high resolution. This dissertation begins by providing the reader with the basic theory of analog/digital (ADC) and its state of the art. The main goal of the work is the design of an ADC based on a Sigma-Delta architecture that meets the necessary medical requirements. The converter was implemented in a 130 nm CMOS technology using a sampling frequency of 1 MHz, with a bandwidth of 1 kHz, and a source voltage of 1.2 V. The integrators of sigma-delta employs an unusual Opamp typology in order to reach a high gain, without resourcing to cascode techniques. The quantizer has a resolution of 1.5 bits and is realized with two dynamic comparators, in order to minimize power consumption.